بيئة اللغة العربية بمعهد الدار السلام برمراءن سومطرة الشمالية: THE ARABIC ENVIRONMENT AT DAAR AS-SALAM ISLAMIC BOARDING SCHOOL IN PARMERAAN NORTH SUMATRA - Syaipuddin Ritonga (Department of Arabic Education of State Collage for Islamic Studies of Mandailing Natal, 2020)
Abstract: The aims of in this research is how the environment of the Arabic language in the Dar Al-Salam Islamic Boarding School in North Sumatra and its role in education. The reseach focused on the environment in the Arabic language at the Dar es Salaam Islamic Boarding School in Parmeraan, the activities of students in acquiring language skills, and the role of the Arabic language environment in education at the Dar Al Salam Institute in Parmeraan. This reseach uses a qualitative approach, it’s starts from the data and use the practical theory to analize and clarify so end up with the new theory. The result of this research, (1) the Arabic language environment at the Dar Al Salam Institute in North Sumatra is divided into two types, artificial and natural environments. (2) The activities of students in acquiring the Arabic language at the Dar es Salaam Institute are influenced by two factors, internal and external. The internal factors are encouragement, talent, and intelligence. And the external factors are the environment, the teacher, materials of study, conservation, tradition, job, incentives, exercises, and teaching media. (3) The role of the Arabic language environment in education consists of three parts, they are the role of the Arabic environment in learning general sciences, the role of the the Arabic environment in learning religious sciences, and the role of the the Arabic environment in learning the Arabic language. And all of part of these environments role was successful. الكلمات الأساسية: بيئة، اللغة العربية